Some Small Sample Properties of Durbin's Tests for Serial Correlation in Regression Models Containing Lagged Dependent Variables - Kenkel, James L. (Econometrica, 1974)
James L. Kenkel, Some Small Sample Properties of Durbin's Tests for Serial Correlation in Regression Models Containing Lagged Dependent Variables, Econometrica, Vol. 42, No. 4 (Jul., 1974), pp. 763-769